2023
DOI: 10.3390/jcm12124030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Use or Rejection of Hearing Aids—A Systematic Review and Meta-Analysis

Susana Marcos-Alonso,
Cristina Nicole Almeida-Ayerve,
Chiara Monopoli-Roca
et al.

Abstract: Purpose: To examine the prevalence of adherence to hearing aids and determine their rejection causes. Methods: This study was conducted according to the Preferred Reporting terms for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We performed an electronic search using PubMed, BVS, and Embase. Results: 21 studies that met the inclusion criteria were selected. They analyzed a total of 12,696 individuals. We observed that the most common causes for positive adherence to hearing aid use included having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A comprehensive systematic review and meta-analysis, focusing on factors influencing hearing aid use or rejection, examined patterns of hearing aid usage for 12696 patients with and without hearing loss and a mean age of 72.7 years [ 26 ]. Their findings indicated that approximately 62% of individuals used their hearing aids, while 38% did not.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive systematic review and meta-analysis, focusing on factors influencing hearing aid use or rejection, examined patterns of hearing aid usage for 12696 patients with and without hearing loss and a mean age of 72.7 years [ 26 ]. Their findings indicated that approximately 62% of individuals used their hearing aids, while 38% did not.…”
Section: Discussionmentioning
confidence: 99%